Impact of Maternal Iron Deficiency Anemia on Pregnancy Outcomes in the Third Trimester: A Study at Shaikh Zayed Medical Complex, Lahore. - AHMED, MUHAMMAD; AALISHAN, MUHAMMAD; JAVED, ABDUR REHMAN; IRFAN, ZOHA; AZIZ, SADIA; HAMZA, AMEER; AKRAM, MUHAMMAD (Pakistan Journal of Medical & Health Sciences, 2025)
Background: Iron Deficiency Anemia (IDA) is a common nutritional issue worldwide, especially during pregnancy. Pregnant women are particularly vulnerable due to increased iron requirements for fetal growth and maternal blood volume expansion. IDA can lead to serious maternal and neonatal complications, including low birth weight (LBW), preterm labor, and increased maternal fatigue and weakness. This study investigates the impact of maternal IDA on pregnancy outcomes during the third trimester at Shaikh Zayed Medical Complex, Lahore. Methodology: A prospective study was conducted on 227 pregnant women between April and September 2023. Participants in their third trimester, with or without IDA, were selected based on inclusion and exclusion criteria. Data were collected through simple random sampling and analyzed using SPSS version 26. A chi-square test was used to evaluate the relationship between IDA and pregnancy outcomes, with p < 0.05 considered statistically significant. Results: Among the 227 participants, 82.4% had IDA. Significant maternal outcomes included fatigue (p=0.059), weakness (p=0.001), and dizziness (p=0.018). Neonates born to IDA mothers had a higher prevalence of LBW (p=0.016). Other factors, such as gestational age and hospital stay duration, were nonsignificant. Conclusion: IDA in the third trimester significantly affects maternal and neonatal health, causing fatigue, weakness, dizziness, and LBW in newborns. Early screening, proper supplementation, and nutrition education are crucial to minimize the adverse effects of IDA during pregnancy. Future studies should include larger sample sizes and long-term impact assessments.